2005
DOI: 10.1002/bjs.4908
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of local disease failure and outcome after salvage surgery in patients with anal cancer

Abstract: In the management of anal cancer, local disease failure is a major clinical problem requiring early detection followed by radical surgery, often accompanied by plastic reconstruction. By implication, these factors favour the centralization of treatment for this uncommon cancer to a multidisciplinary oncology team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
3
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(118 citation statements)
references
References 36 publications
5
102
3
8
Order By: Relevance
“…There are few data available about predictors of local failure, but one retrospective study was identified [42]. Renehan and colleagues evaluated outcomes of 254 patients with anal cancer treated with either radiotherapy alone (n ϭ 127) or combined chemoradiation (n ϭ 127) between 1988 and 2000 at a hospital in the United Kingdom.…”
Section: Persistent or Recurrent Diseasementioning
confidence: 99%
“…There are few data available about predictors of local failure, but one retrospective study was identified [42]. Renehan and colleagues evaluated outcomes of 254 patients with anal cancer treated with either radiotherapy alone (n ϭ 127) or combined chemoradiation (n ϭ 127) between 1988 and 2000 at a hospital in the United Kingdom.…”
Section: Persistent or Recurrent Diseasementioning
confidence: 99%
“…São dados semelhantes aos da literatura que mostraram eficácia entre 50 e 90% dos doentes, dependendo do tamanho do tumor 23 e do estádio da doença. 33 Também foi citado que a RT/QT é menos eficaz nos doentes mais idosos. 33 Conseguimos a remissão completa em todos os tumores nos estádios mais iniciais (I e II) e em 75% daqueles nos estádios IIIa e IIIb.…”
Section: Discussionunclassified
“…33 Também foi citado que a RT/QT é menos eficaz nos doentes mais idosos. 33 Conseguimos a remissão completa em todos os tumores nos estádios mais iniciais (I e II) e em 75% daqueles nos estádios IIIa e IIIb. Já entre os tumores da margem anal o controle cirúrgico foi obtido nos dois doentes, sendo que a RT/QT foi realizada posteriormente.…”
Section: Discussionunclassified
“…For example, a study of 308 patients in the Stockholm region of Sweden found that patients treated with neoadjuvant platinum-based chemotherapy had significantly better complete response rates and increased overall five-year survival than patients treated with radiotherapy with or without bleomycin [15]. In the UK, a series of 254 treated at a regional cancer centre demonstrated that chemoradiotherapy was associated with a significant improvement in local control in comparison to radiotherapy alone and this effect persisted six years after initial treatment [16].…”
Section: Yorkshire Datamentioning
confidence: 99%